BEST PRACTICE GAYA KEPEMIMPINAN VISIONER DI SD UNGGULAN MUSLIMAT NU KUDUS - Hamid, Abdulloh; Andriyani, Santi (QUALITY, 2017)
This study aims to determine the visionary leadership style, implementation of visionary leadership strategy of Primary Elementary School Muslimat NU Kudus District. This research uses qualitative approach of phenomenology. The study was conducted at the Primary Element of Muslimat NU Kudus. Data collection using interview techniques, observation, and documentation. Research subject is principal. Validity of data in this research with various evidence findings of interviews, documentation, real conditions of the field as a phenomenon or social reality experienced. Data analysis was done by using interactive model. Miles & Huberman through the meaning of data presented in the field and.